Kinetic and physical studies of beta-lactamase inhibition by a novel penem, BRL 42715. - Farmer, T H (1994)
The interactions of Staphylococcus aureus, Bacillus cereus I, TEM, Klebsiella pneumoniae K1 and Enterobacter cloacae P99 beta-lactamases with the novel penem inhibitor BRL 42715 were investigated kinetically and, in some cases, by electrospray mass spectrometry (e.s.m.s.). All the beta-lactamases were rapidly inactivated by BRL 42715, with second-order rate constants ranging from 0.17 to 6.4 microM-1.s-1. The initial stoichiometry of beta-lactamase inhibition was essentially 1:1, with the exception of the K1 enzyme. In this instance about 20 molecules of BRL 42715 were hydrolysed before the enzyme was completely inhibited. Inhibited beta-lactamases did not readily regain activity in the absence of BRL 42715, the half-lives for regeneration of free enzyme ranging from 5 min for the K1 beta-lactamase to over 2 days for the staphylococcal enzyme. Recovery of activity was incomplete for TEM-1, K1 and P99 beta-lactamases, suggesting partitioning of the inhibited enzymes to give a permanently (or at least very stable) inactivated species. Examination of the interactions of the penem with TEM, B. cereus I and P99 beta-lactamases by e.s.m.s. also showed rapid and stoichiometric binding of the inhibitor. In all cases a mass increase of 264 Da over the native enzyme was observed, corresponding to the molecular mass of BRL 42715, showing that no fragmentation of the penem occurred on reaction with the beta-lactamases.